Using the 2020 global pandemic as a springboard to highlight the need for amphibian conservation in eastern Asia. (March 2021) - Borzée, Amaël; Kielgast, Jos; Wren, Sally; Angulo, Ariadne; Chen, Shu; Magellan, Kit; Messenger, Kevin R.; Hansen-Hendrikx, Candace M.; Baker, Anne; Santos, Marcileida M. Dos; Kusrini, Mirza; Jiang, Jianping; et al.
Abstract: Emerging infectious diseases are on the rise in many different taxa, including, among others, the amphibian batrachochytrids, the snake fungal disease and the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) virus, responsible for Coronavirus disease 2019 (COVID-19) in mammals. Following the onset of the pandemic linked to COVID-19, eastern Asia has shown strong leadership, taking actions to regulate the trade of potential vector species in several regions. These actions were taken in response to an increase in public awareness, and the need for a quick reaction to mitigate against further pandemics. However, trade restrictions rarely affect amphibians, despite the risk of pathogen transmission, directly, or indirectly through habitat destruction and the loss of vector consumption. Thus, species that help alleviate the risk of zoonoses or provide biological control are not protected. Hence, in view of the global amphibian decline and the risk of zoonoses, we support the current wildlife trade regulations and support measures to safeguard wildlife from overexploitation. The current period of regulation overhaul should be used as a springboard for amphibian conservation. To mitigate risks, we suggest the following stipulations specifically for amphibians. I) Restrictions to amphibian farming in eastern Asia, in relation to pathogen transmission and the establishment of invasive species. II) Regulation of the amphibian pet trade, with a focus on potential vector species. III) Expansion of the wildlife trade ban, to limit the wildlife-human-pet interface. The resulting actions will benefit both human and wildlife populations, as they will lead to a decrease in the risk of zoonoses and better protection of the environment. Significance statement: There is an increasing number of emerging infectious diseases impacting all species, including amphibians, reptiles and mammals. The latest threat to humans is the virus responsible for COVID-19, and the resulting pandemic. Countries in eastern Asia have taken steps to regulate wildlife trade and prevent further zoonoses thereby decreasing the risk of pathogens arising from wild species. However, as amphibians are generally excluded from regulations we support specific trade restrictions: I) Restrictions to amphibian farming; II) regulation of the amphibian pet trade; III) expansion of the wildlife trade ban. These restrictions will benefit both human and wildlife populations by decreasing the risks of zoonoses and better protecting the environment. Highlights: Eastern Asia showed strong leadership in regulating the trade of potential vector species following the COVID-19 pandemic. Trade restrictions rarely affect amphibians despite direct (transmission) and indirect risk (vector control). We support the current wildlife trade regulations and measures to safeguard wildlife from overexploitation. Recommendations: I) Restrictions to amphibian farming in eastern Asia. II) Regulation of the amphibian pet trade. III) Expansion of the wildlife trade ban, to limit the wildlife-human-pet interface.